2013
DOI: 10.1038/ajg.2013.305
|View full text |Cite
|
Sign up to set email alerts
|

Covered Self-Expandable Metal Stents With an Anti-Migration System Improve Patency Duration Without Increased Complications Compared With Uncovered Stents for Distal Biliary Obstruction Caused by Pancreatic Carcinoma: A Randomized Multicenter Trial

Abstract: By preventing tumor ingrowth and migration, covered SEMSs with an anti-migration system had a longer duration of patency than uncovered SEMSs, which recommends their use in the palliative treatment of patients with biliary obstruction due to pancreatic carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
210
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(226 citation statements)
references
References 39 publications
10
210
3
3
Order By: Relevance
“…The specific advantages and disadvantages of each type of stent remain unclear [13][14][15][16][17][18][19][20]. However, previous studies have concluded that the time to RBO is longer for CSEMS than UCSEMS [13,[18][19][20].…”
Section: Discussionmentioning
confidence: 94%
“…The specific advantages and disadvantages of each type of stent remain unclear [13][14][15][16][17][18][19][20]. However, previous studies have concluded that the time to RBO is longer for CSEMS than UCSEMS [13,[18][19][20].…”
Section: Discussionmentioning
confidence: 94%
“…Endoscopic clipping [15] can reduce the hazard of stent migration, especially in those related with esophago-pleural fistulas without luminal obstruction. Covered SEMS with an anti-migration system [16] with uncovered long flared ends has a longer life and lesser risk of migration; therefore they are beneficial in the palliative treatment of patients.…”
Section: Discussionmentioning
confidence: 99%
“…SEMSs are considered superior to plastic stents with large bores in terms of stent patency [3][4][5][6], but it remains challenging to determine which type of SEMS is optimal for the palliation of distal biliary obstruction due to stent-related adverse events that cause recurrent biliary obstruction [7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%